2012
DOI: 10.3354/esr00454
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive evaluation of physiological stress hormone responses in a captive population of the greater bilby Macrotis lagotis

Abstract: Captive breeding programs are increasingly being used as a management option for threatened mammals. The greater bilby Macrotis lagotis, for example, is a vulnerable species which is maintained in captivity at several facilities in Australia. Non-invasive evaluation of stress hormones (cortisol in mammals) via excretory metabolites can be used to monitor physiological stress responses of captive individuals. In this study, we validated an enzyme-immunoassay (EIA) to measure cortisol metabolites in fresh faecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…This short-term increase in corticosterone promotes key changes in behaviour and physiology that enable individuals to cope with stress [610]. Some of the key behaviours affected by corticosterone in amphibians and also in other vertebrates (small mammals and lizards) include initiation of hiding and defensive behaviours [1113], increased locomotor activity [14,15], and increased thermoregulatory behaviour [16,17]. The sight of a predator can induce a corticosterone response in birds [18] and exposure to predator odour can induce corticosterone responses in male Sprague–Dawley rats [19].…”
Section: Introductionmentioning
confidence: 99%
“…This short-term increase in corticosterone promotes key changes in behaviour and physiology that enable individuals to cope with stress [610]. Some of the key behaviours affected by corticosterone in amphibians and also in other vertebrates (small mammals and lizards) include initiation of hiding and defensive behaviours [1113], increased locomotor activity [14,15], and increased thermoregulatory behaviour [16,17]. The sight of a predator can induce a corticosterone response in birds [18] and exposure to predator odour can induce corticosterone responses in male Sprague–Dawley rats [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial that we characterise how wildlife respond to research and conservation interventions such as capture and handling (de Villiers et al 1995;Narayan et al 2012) and translocation (Kahn et al 2007) to assess risk, minimise harm and increase the efficacy of these activities. For example, it has been suggested that the stress of translocation is associated with increased risk of infectious disease in translocated wildlife (Teixeira et al 2007;Dickens et al 2010;Sainsbury and Vaughan-Higgins 2012), including recrudescence of latent and normally innocuous pathogens as well as increased vulnerability to diseases at the release site to which the translocated animals may not have been previously exposed (Mihok et al 1992).…”
Section: (3) Wildlife Management Interventionsmentioning
confidence: 99%
“…We analysed bilby fecal extracts for concentrations of FCM using enzyme immunoassay (EIA) previously described for other mammals (Wielebnowski et al 2002;Millspaugh and Washburn 2004), and recently used for a captive subpopulation of the greater bilby (Narayan et al 2012;Evans et al 2013). Laboratory validation was done using accuracyrecovery checks and parallelism.…”
Section: Fecal Sampling: Captivementioning
confidence: 99%
“…This major contraction in range is primarily attributed to predation from introduced species (e.g., red fox [Vulpes vulpes] and feral cats [Felis catus]), habitat destruction through agriculture and competition with introduced herbivores (Moseby et al 2009). Whilst information on the bilby's reproductive biology, anatomy and behaviour are available, literature on its stress physiology is only from single captive population (Narayan et al 2012). There is no information available on FCM levels in semi-wild populations of this marsupial.…”
Section: Introductionmentioning
confidence: 99%